Recent advances in analytical strategies and microsystems for food allergen detection. (1st March 2022) - Shin, Jae Hwan; Reddy, Y. Veera Manohara; Park, Tae Jung; Park, Jong Pil
Highlights: Summarized conventional methods to novel methods of food allergen detection. Current limitations and insights of food allergen detection are addressed. The challenge and outlook of on-site detection food allergens technologies are discussed. Abstract: Food allergies are abnormal immune responses that typically occur within short period after exposure of certain allergenic proteins in food or food-related resources. Currently, the means to treat food allergies is not clearly understood, and the only known prevention method is avoiding the consumption of allergen-containing foods. From the viewpoint of analytical methods, the effective detection of food allergens is hindered by the effects of various treatment processes and food matrices on trace amounts of allergens. The aim of this effort is to provide the reader with a clear and concise view of new advances for the detection of food allergens. Therefore, the present review explored the development status of various biosensors for the real-time, on-site detection of food allergens with high selectivity and sensitivity. The review also described the analytical consideration for the quantification of food allergens, and global development trends and the future availability of these technologies.